The Influence of Spiritual Intelligence on Leadership Competency in The Scope of Government Institutions - Dian Novita Siswanti; Rozainee Khairuddin; Fatimah Wati Halim (Indonesian Journal of Learning Education and Counseling, 2021)
The success of an organization cannot be separated from the quality of a leader. Leaders have an important role in achieving the success of an organization. For this reason, a competent leader is needed, so that he is able and proficient in managing the system applied in an organization. This study aims to determine the effect of spiritual intelligence on leadership competencies of leaders within the scope of government agencies. Subjects in this study, leaders within the scope of government totaling 300 leaders in the Makassar City Government Authority. The measuring instrument used is based on the Emmons and Swiderski theory. The statistical analysis method applied is the ordinal regression analysis. Hypothesis test results showed that spiritual intelligence affects leadership competence (p = 0.000), with a contribution of 6.9%. This research implies that it becomes the input for leaders to increase the level of spiritual intelligence so that they can become competent leaders in carrying out their duties and responsibilities, and can implement systems and manage human resources to achieve maximum results from organizational goals.